Competition among wild rice, landrace, improved cultivar and F1 hybrid rice - Joshi, Bal Krishna; Gyawali, Sanjaya; Sah, Surya Narayan; Chaudhary, Rewati Raman (Journal of Agriculture and Environment, 2018)
Four genotypes, namely Oryza rufipogon, F1 of IR68888A/Chaite-6, Chaite-6 and Ratodhan were grown in crop and competition environment at Rampur, Nepal to study the effect of genotypes mixture on the characters. Univariate, multivariate and correlation methods of analysis were applied. Seven characters namely panicle length, panicle number, grain yield, harvest index, internode length and leaf width showed significantly different response in crop and competition environment. The performance of cultivar was poor in competition environment than hybrid and wild rice. Hybrid and wild rice showed longer panicle length in competition environment. Significant reduction in panicle number was found in cultivars. The pattern of tiller number over the growth period showed that the competition started after 50 days of seeding. Grain yield of cultivars was significantly reduced in competition environment. Considering the most important characters, hybrid was best competitor and local landrace (Ratodhan) was poorest competitor. Significant variations in culm characters were not found between two environments but leaf characters varied significantly. Highest increment in plant height was found in F1 grown in competition than crop environment. Relationship between characters was affected by growing environment. Among 162 pairs of characters r-value of six and 36 pairs were highly significant different from zero in crop and competition environment respectively. Multivariate analysis indicates that growing environment does not suppress the genetic characters. Competition among the tested genotypes exists even in the recommended spacing. Competition should be studied in detail planting at different spacing.